12.8k views
0 votes
Which equation is equivalent to 7(r + 4) - 3?

7*r+7*4*3
7*r*7*4-3
7*r+7*4-3
7*r+7*4

1 Answer

5 votes

Answer: Choice C

7*r+7*4-3

=========================================================

Reason:

We use the distributive property to go from 7(r+4) to 7*r+7*4

Multiply the outer 7 by each term inside.

Then the -3 tags along without any changes to it

So we go from 7(r+4) - 3 to 7*r+7*4 - 3

This can be simplified further to 7r+25, but your teacher has chosen not to simplify at this time.

User Felix Fong
by
4.8k points